A new mixing chamber geometry design for supersonic ejector performance optimization using computational fluid dynamics - Amer Muzaber; Nadin Bassmaji; Assem Kaddah (International Journal of Thermofluids)
Jet refrigeration systems have limited usage due to their low coefficient of performance, which depends on ejector performance. Improving supersonic ejectors’ performance has been a focus for many researchers, as they serve as alternative devices using low-grade thermal sources. This study primarily aims to improve the design of supersonic ejectors, moving away from the traditional CPM design toward a more efficient new design using CFD software. A new curved shape of the mixing chamber is proposed, characterized by an arc with radius (r). Ten distinct profiles of curved mixing chamber with fixed geometries for the ejector throat, diffuser, and primary nozzle are investigated within a boiler saturation temperature range of 130°C to 170°C and an evaporator temperature of 7.5°C. The proposed design shows a notable increase in the entrainment ratio, coinciding with a reduction in critical backpressure. For instance, at a boiler temperature of 170°C, the entrainment ratio increases by up to 37 %, accompanied by a 10 % decrease in critical backpressure. Thus, ejector performance is assessed via ejector efficiency. The curved mixing chamber shows superior efficiency compared to the conventional design at elevated boiler temperatures. Notably, there is one optimal radius that offers the best performance at each boiler temperature. Simulation results also indicate that the entrainment ratio decreases as the boiler temperature increases, a common observation for supersonic ejectors. The findings are explained based on flow contours and fluid parameter distributions.